The Role of Geographic Information Systems in Marketing Strategy: Improving the Efficiency of Store Locations and Consumer Targeting Based on Alfamart Locations in Bandung City - Syaifuddin, Syaifuddin; Puad, Noor Aimi Mohamad; Rusdian, Suca (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
This research explores the application of Geographic Information Systems (GIS) to optimize location selection and consumer targeting strategies for Alfamart mini markets in Bandung City. The purpose of this study is to assess how GIS can improve the decision-making process in determining the location of new outlets by integrating spatial data with multi-criteria decision analysis methods. This research uses Analytical Hierarchy Process (AHP) to evaluate the best location based on factors such as population density, accessibility, and the presence of competitors. Additionally, authors conducted consumer segmentation using the K-means clustering technique to understand consumer behavior based on shopping patterns and geographical distribution. Key findings showed that the Dago area in Bandung was the optimal location for the new store, with a 25% increase in foot traffic and a 30% increase in sales during the first three months of operation. This research emphasizes the importance of using GIS not only for spatial analysis but also for more targeted marketing, improved operational efficiency, and customer satisfaction. However, there are limitations in terms of dependence on data quality and the dynamics of consumer preferences. Future research could expand the coverage area and integrate additional variables to refine the application of GIS in retail location planning.